Tackling Real-World Environmental Paper Pollution: A Problem-Based Microbiology Lesson About Carbon Assimilation - Shay, Jackie E.; Solis, Ruth; García-Ojeda, Marcos E. (Frontiers in Microbiology, 2020)
Governmental and educational organizations advocate for the adoption of inquiry-based, student-centered educational strategies in undergraduate STEM curricula. These strategies are known to benefit students by increasing performance, enhancing mastery of class content, and augmenting affect, particularly in underrepresented racial/ethnic minority students. Among these strategies, case study and project-based learning allow students to master course content while collectively tackling relevant, real-world societal problems. In particular, environmental pollution with paper-based products provide a current problem by which microbiology students learn about the role of microorganisms in paper waste management as well as the microbiological and biochemical processes involved in protein secretion, nutrient uptake, and energy metabolism. Delivered in a flipped hybrid class in a Technology-Enabled Active Learning (TEAL) laboratory, this lesson taught students about exoenzyme secretion, biomolecular hydrolysis, intracellular transport of sugars, and sugar catabolic reactions. Students demonstrated increased comprehension of exoenzymes function and secretion, as well as how cells uptake the products of exoenzyme hydrolysis. However, students had challenges in placing the transported exoenzyme products within metabolic processes. Our results show increased perceived learning from the students as well as an understanding of the societal implications of these microbiological concepts. Our lesson deviated from knowledge silos in which students learn information in discrete topics. While departing from employing traditional, compartmentalized learning approaches, this student-centered guided lesson frames the systemic nature of the microbiological and biochemical processes underlying the decomposition of organic matter in a real-world context.